The Effect of Cutting Speed Variation, Feeding and Depth of cut on Lathe Machine Against Surface Roughness of Workpiece ST 37 - Mohammad Baihaqi,Fathur Rhohman, Irwan Setyowidodo (International Conference on Industrial Revolution for Polytechnic Education, 2021)
This research is based on background behind the results of observations and experiences researcher, that process especially the surface turning is strongly influenced by the cutting angle of the tool,feeding,cutting speed ,depth of cut and others. Problem of this research is how the influence of variation feeding,cutting speed ,depth of cut on the use of the lathe process to the level of roughness workpiece surface ST 37. This research uses factorial method 2k K is variable. The variables used in this research are cutting speed (50 m / min and 80 m / min), depth of cut (0.3 mm and 0.7 mm) and feeding (0.07 mm / rev - 0.09 mm / rev).The conclusions of the results of this study are cutting speed and depth of cut have significant influence against surface roughness, where as the rate of infestation is not significant effect on surface roughness. because the cutting speed and depth of cut has a F-value greater than Ftable. Based on the conclusions of the results of this study, it is recommended: To obtain optimum surface roughness is to use lowest cutting speeds and lowest depth of cut while the feeding can be set at maximum conditions because no significant effect on surface roughness.In this study the optimum surface roughness obtained was 1.90 µm under experimental conditions; cutting speed 80 m / min (lowest), feeding 0.09 mm / rev (low) and depth of cut 0.3 mm (lowest).